Introduction: Investigating Explicit L2 Grammar Instruction Through Multiple Theoretical and Methodological Lenses. Issue 1 (18th April 2022) - Toth, Paul D.
Abstract: The articles in this special issue apply a variety of theoretical and methodological perspectives to quantitative and qualitative data gathered in eight third‐year, intermediate second‐language (L2) Spanish classes at three U.S. high schools (N = 195). The goal of this research was to document grammatical development through two forms of explicit instruction on the pronoun se : one involving deductive rule presentations, and the other involving an inductive "co‐construction" of grammatical rules with learners (Adair‐Hauck et al., 2005). After reviewing cognitive and social approaches to explicit instruction, I present the context and procedures for data gathering, followed by an overview of the main findings in each article. While quantitative results suggest a somewhat stronger performance for the deductive group, qualitative evidence suggests a more challenging task for teachers implementing co‐construction. I conclude emphasizing the value of high‐quality explicit instruction to L2 development and the importance of teachers in making that happen. Abstract :